Nickel oxide nanoparticles can recruit eosinophils in the lungs of rats by the direct release of intracellular eotaxin. Issue 1 (December 2015) - Lee, Seonghan; Hwang, Sung-Hyun; Jeong, Jiyoung; Han, Youngju; Kim, Sung-Hyun; Lee, Dong-Keon; Lee, Hae-Suk; Chung, Seung-Tae; Jeong, Jayoung; Roh, Changhyun; Huh, Yun; Cho, Wan-Seob
Abstract Background Instillation of highly soluble nanoparticles (NPs) into the lungs of rodents can cause acute eosinophilia without any previous sensitizations by the role of dissolved ions. However, whether gradually dissolving NPs can cause the same type of eosinophilia remains to be elucidated. We selected nickel oxide (NiO) as a gradually dissolving NP and evaluated the time course pulmonary inflammation pattern as well as its mechanisms. Methods NiO NPs were intratracheally instilled into female Wistar rats at various concentrations (50, 100, and 200 cm2 /rat) and the lung inflammation was evaluated at various time-points (1, 2, 3, and 4 days). As positive controls, NiCl2 and the ovalbumin-induced allergic airway inflammation model was applied. NiCl2 was instilled at 171.1 μg Ni/rat, which is equivalent nickel concentration of 200 cm2 /rat of NiO NPs. Cytological analysis and biochemical analysis including lactate dehydrogenase (LDH), total protein, and pro-inflammatory cytokines were measured in bronchoalveolar lavage fluid (BALF). The levels of total immunoglobulin E (IgE) and anaphylatoxins (C3a and C5a) were measured in BALF and serum. The levels of eotaxin were measured in the alveolar macrophages and normal lung tissue before and after addition of cell lysis buffer to evaluate whether the direct lysis of cells can release intracellular eotaxin. Results NiO NPs produced acute neutrophilic inflammation throughout the study. However, eosinophils were recruited at 3 and 4 days post-instillation of NiO NPs and the magnitude and pattern of inflammation was similar with NiCl2 at 24 h post-instillation. The eosinophil recruitment by NiO NPs was not related with either the levels of total IgE or anaphylatoxins. The lysis of alveolar macrophages and normal lung tissue showed high levels of intracellular eotaxin and the levels of LDH showed positive correlation with the levels of eotaxin. Conclusions Instillation of NiO NPs produced neutrophilia at 1 and 2 days after instillation, while the mixed type of neutrophilic and eosinophilic inflammation was produced at 3 and 4 days post-instillation, which was consistent with NiCl2 . The mechanism of the eosinophilia involves the direct release of intracellular eotaxin due to the rupture of cells by the accumulated solubilized nickel ions in the phagolysosome.